Feed blocks as a supplement for goat kids grazing natural Tunisian rangeland during the dry season - Gasmi-Boubaker, A; Kayouli, C; Buldgen, A (ANIMAL FEED SCIENCE AND TECHNOLOGY, 2006)
Two experiments were conducted to investigate the effects of PEG and feed blocks on digestion of shrub species consumed by goats (experiment 1) and kid growth while browsing during the dry season (experiment 2). In experiment 1, in vitro gas production was determined using a rumen fermenter. Six shrub species were incubated separately (Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber, and Viburnum tinus). Effects of polyethylene glycol (PEG 4000) and feed block supply were investigated. In experiment 2, 21 local kids, 18.75 (+/- 1.4) kg body weight (BW) were allowed to browse in shrub-lands and allocated to three treatments in a production trial lasting 147 days (July-December). Control group receive no supplement, whereas the two other groups received either PEG-free (13) or PEG-containing feed blocks (B-PEG). All shrubs were low in crude protein (59-91 g kg(-1) dry matter) but high in total condensed tannins; mean content was 43 g kg(-1) DM (8.8-65) for bound condensed tannin and 205 g kg(-1) DM (10.8-363) for free condensed tannin. Gas volume produced after 24 h differed among shrub species (P < 0.05). V tinus produced the highest volume (77.8 ml g(-1) organic matter) and Q. suber the lowest (35 ml g-1 OM). The mean rate of fermentation was 0.135h(-1) (0.121-0.150 h(-1)). PEG addition increased gas production by 48.5%, volatile fatty acid by 38.4% and organic matter fermented by 41.7% of the mixture of shrubs (P < 0.05). In the practical trial, the use of blocks with and without PEG avoided BW loss of the goats under dry season. While the control group lost 19 g day(-1), the bloc supplemented groups grew at 12 g day(-1) (-PEG) and 24 (+PEG) g day(-1). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: feed blocks; Gas production; Goat; PEG; Shrubs

Feed blocks as a supplement for goat kids grazing natural Tunisian rangeland during the dry season - Gasmi-Boubaker, A.; Kayouli, C.; Buldgen, A. (ANIMAL FEED SCIENCE AND TECHNOLOGY, 2006)
Two experiments were conducted to investigate the effects of PEG and feed blocks on digestion of shrub species consumed by goats (experiment 1) and kid growth while browsing during the dry season (experiment 2). In experiment 1, in vitro gas production was determined using a rumen fermenter. Six shrub species were incubated separately (Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber, and Viburnum tinus). Effects of polyethylene glycol (PEG 4000) and feed block supply were investigated. In experiment 2, 21 local kids, 18.75 (+/- 1.4) kg body weight (BW) were allowed to browse in shrub-lands and allocated to three treatments in a production trial lasting 147 days (July-December). Control group receive no supplement, whereas the two other groups received either PEG-free (13) or PEG-containing feed blocks (B-PEG). All shrubs were low in crude protein (59-91 g kg(-1) dry matter) but high in total condensed tannins; mean content was 43 g kg(-1) DM (8.8-65) for bound condensed tannin and 205 g kg(-1) DM (10.8-363) for free condensed tannin. Gas volume produced after 24 h differed among shrub species (P < 0.05). V tinus produced the highest volume (77.8 ml g(-1) organic matter) and Q. suber the lowest (35 ml g-1 OM). The mean rate of fermentation was 0.135h(-1) (0.121-0.150 h(-1)). PEG addition increased gas production by 48.5%, volatile fatty acid by 38.4% and organic matter fermented by 41.7% of the mixture of shrubs (P < 0.05). In the practical trial, the use of blocks with and without PEG avoided BW loss of the goats under dry season. While the control group lost 19 g day(-1), the bloc supplemented groups grew at 12 g day(-1) (-PEG) and 24 (+PEG) g day(-1). (c) 2005 Elsevier B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: feed blocks; Gas production; Goat; PEG; Shrubs